2003
DOI: 10.1046/j.1523-1755.2003.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct involvement of the receptor-mediated apoptotic pathways in cisplatin-induced renal tubular cell death

Abstract: Based on these data, we conclude that the Fas- and TNFR1-mediated apoptotic pathways are directly involved in the pathogenesis of cisplatin-induced RTC death process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
169
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(188 citation statements)
references
References 39 publications
12
169
1
2
Order By: Relevance
“…Thus regulation of the expression of executioner caspases is crucial prior to the execution of cell death. Several studies including ours have previously demonstrated activation of executioner caspases (caspase-3/7 and -6) in both in vitro 12,13 and in vivo 14,15 models of cisplatin-induced AKI. Similarly, induction of p53 transcription factor was demonstrated in RTECs in both in vitro [16][17][18] and in vivo 19 studies of cisplatin AKI.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Thus regulation of the expression of executioner caspases is crucial prior to the execution of cell death. Several studies including ours have previously demonstrated activation of executioner caspases (caspase-3/7 and -6) in both in vitro 12,13 and in vivo 14,15 models of cisplatin-induced AKI. Similarly, induction of p53 transcription factor was demonstrated in RTECs in both in vitro [16][17][18] and in vivo 19 studies of cisplatin AKI.…”
mentioning
confidence: 64%
“…Our previous study showed that the activity of caspase-1 is not increased in response to cisplatin in kidney cells. 12 Caspase-3 is predominately activated in a p53-dependent manner in cisplatin injury in RTECs 12,13 and in vivo in cisplatin nephrotoxicity but, like initiator caspases, it was not found to be a transcriptional target of p53. In fact, no p53-binding element was found in the caspase-3 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on its concentration, cisplatin induces necrosis as well as apoptosis in these cells, leading to acute renal failure. Multiple signaling pathways are activated by cisplatin in renal tubular cells (Baliga et al, 1998;Megyesi et al, 1998;Shiraishi et al, 2000;Kaushal et al, 2001;Nowak, 2002;Park et al, 2002;Ramesh and Reeves, 2002;Liu and Baliga, 2003;Tsuruya et al, 2003;Arany et al, 2004;Li et al, 2004;Sheikh-Hamad et al, 2004;Yu et al, 2005); however, it is unclear how these signals are integrated to determine cell injury and death (Arany and Safirstein, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…1 In previous animal studies, we and others have demonstrated an important role for TNF-␣ in the pathogenesis of cisplatin-induced renal injury. [2][3][4][5][6] Inhibition of TNF-␣ production or action markedly reduced the nephrotoxicity of cisplatin. 2,3 Stimulation of TNF-␣ production in the kidney by cisplatin involved both a stabilization of TNF-␣ mRNA 7 and a p38 MAPK-dependent increase in TNF-␣ mRNA translation, 4 however, the upstream signals responsible for TNF-␣ production remain unclear.…”
mentioning
confidence: 99%